Evaluation of Efficiency of Plant Extracts and fungal Culture Filterates in biological control of fungal growth associated withTomato and Okra seeds - S.SaadonAbdul – Ameer; Abdul – Ameer k.Saba (Al-Qadisiyah Journal of Pure Science, 2017)
The study included testing the efficacy of alcoholic extracts treatments for roots of alfalfa plant(Medicago sativa L.)and rhizomes of turmeric(Curcuma longa L.)and fungal filtrates of Trichoderma harzianum and Penicillum digitatum in the fungi that associated for Tomato and Okra seeds, and study the effect this treatment in radial growth some fungi isolated from this seeds . The results showed isolated several species of seed borne fungi of Tomato and Okra sterilized and unsterilized,and idenitification six species of it with different frequency ratio, and this species are: Aspergillus niger, Alternaria alternata, Fusarium solani, Fusarium oxysporum ,Curvularia lunata ,Penicillum notatum. The results showed that there is signiference difficant in growth of tested fungi on soild culture medium(PDA)in measuring with controlled treatment at level of possibility 5% and these fungi are A. alternata,F. solani, C. lunata, and antagonistic fungal filtrates T. harzianum was the most effective on A. alternata and F. solani The percentage of radial growth inhibition of this fungi at concentration15%reached about(89.75-86.92)% respectivety,whereas alcoholic alfalfa extract was the most effective extract on C. lunata about (88.46)and antagonistic fungal filtrates P. digitatum at concentration 15% was the least activity among them with percentage of inhibition about(70.62-76.67-73.95)% respectively.